Real Time Water Quality Monitoring System for Smart City in Malaysia - Mohd Hariz Amin; Aznida Abu Bakar Sajak; Juliana Jaafar; Husna Sarirah Husin; Salina Mohamad (Universitas Pendidikan Indonesia (UPI), 2022)
Water is essential for life. Frequent water disruption in Malaysia caused turbulence in daily lives and livelihood of thousands Malaysian. The water operators in Malaysia are facing serious challenges to ensure consumers have continuous access to clean water and to ensure a sustainable water future. River pollution in Malaysia had been identified to be one of the causes of water crisis in Malaysia. Hence, a continuous monitoring system utilizing the concept of Internet of Things had been proposed in this paper. Agile model is used due to its simplicity. The water’s pH measurement, turbidity, temperature and flow can be measured and the reading will be sent to end-user. The sensors that detects the pH value, turbidity, temperature and flow measurement of a water sample will pass through the information to the Arduino, and the result will be shown on the mobile devices via an app called Blynk. This portable and comprehensive prototype is suitable to be used in Smart Cities where WiFi signals is available as the transmission medium.